"The burgers that done the deed": Hazardous food in Thomas Pynchon’s ’Inherent Vice’ - Ramalhete Gomes, Miguel (Cadernos de Literatura Comparada (teste), 2017)
Thomas Pynchon’s Inherent Vice (2009), recently adapted into film by Paul Thomas Anderson (2014), depicts “countercultural California [as] a lost continent of freedom and play, swallowed up by the faceless forces of co-optation and repression”, to use the words of Louis Menand in The New Yorker (2009). While tracking the meandering investigations of Larry “Doc” Sportello, a doped-up private detective, Pynchon composes an elegy for the dwindling late-1960s hippy utopia about to disappear in the wake of a general transformation of the US into an increasingly corporatized, surveyed, and normalised space. This essay explores the role of hazardous and unhealthy food in characterising the anarchic utopia of late-1960s Californian counterculture. Like its often explosive or toxic food, this counterculture suffers from a tendency to deteriorate due to the essential instability of its components, which is, in fact, the very definition of “inherent vice”. Yet, such references, though perhaps unappetising, contribute to an affirmative, if eulogistic portrayal of such a culture. In a contemporary context of increasing food and health regulation, often targeted at traditional and unusual forms of food, this essay aims to discuss the main, and frequently vivid, references to food and drink in Pynchon’s novel as signifiers of a larger tendency to escape restrictive social norms, as well as health inspections.